Advanced ultrasound-guided biopsy simulation training using cadaveric phantoms: cadaver day. Issue 10 (October 2020) - McNeill, A.; Anstee, A.; Hoare, T.
Highlights: Cadaveric phantoms provide a high quality experience for practicing US guided biopsies. Groups of learners can be taught simultaneously on a single training day. Each learner is guaranteed the opportunity to make multiple needle passes. Registrars do not have to compete in a busy clinical environment to achieve this exposure. Registrars and patients avoid the risk of an adverse outcome. Faculty get a strong sense of level of competency of each learner.